An exploratory study of constitutional design in three island states: Seychelles, Comoros, and Mauritius. Issue 3 (3rd July 2017) - Poupko, Eliezer S.
ABSTRACT: This article explores the effects of constitutional design on conflict management and democratisation outcomes in three African island states: Seychelles, Comoros, and Mauritius. As an exploratory framework, the article reflects upon Arend Lijphart's theory of accommodative constitutional design in view of political developments in the three cases, beginning around their independence and continuing into recent times. The case studies provide some general support to Lijphart's accommodative theory, and particularly to the need to facilitate broad representation and an overall sense of political inclusion, but they also raise critical questions regarding the effects of his institutional recommendations. Contrary to Lijphart's approach, majoritarian legislative elections might under certain conditions facilitate greater inclusion than proportional representation, and direct presidential elections could sometimes be more inclusive than a parliamentary executive. The findings on Lijphart's recommendations of group autonomy are less clear, particularly regarding the question of whether territorial autonomy might increase risks of secession.